O Som da Aura de Hermeto Pascoal e a possibilidade de utilização em arranjo coral - Lima, Rômulo Augusto Pereira de (Brasil, 2024)
The arrangement method Som da Aura has been expored among different contexts, but so far, there is no knowledge of it being used in a choir arrangement. So, this work is about a four voice arrangement development of the song “Caminhos de Rio” of the musical group “Raízes Caboclas”, having on it interview pieces of the group founder, Celdo Braga. These vocal excerpts, within the four voices in distinct moments, tried to be faithful to Celdo Braga’s spoken voice and served as raw material to the Som da Aura.